Semiotic knowledge about mass communication Umberto Eco and problems of comprehension of digital reality - T. Smirnova; I. Unzhakova (Цифровая социология, 2019)
Classical sociological theories have enormous potential for explaining social objects, phenomena, and processes, including those taking place in a modern informational society. Among these classics is owned Umberto Eco - an Italian scholar, literary critic, publicist and writer, is among those classics. Some aspects of the scientific heritage of Umberto Eco about semiotic analysis, signs and interpretation of their meanings, mass communication in relation to the tasks of studying virtual communications, the Internet, network society and the digital economy have been revealed. The phenomenon of “visual communication” has been considered in detail: in natural language, the value is predetermined, in the visual it is generated as the message is received. It is assumed that not all communicative phenomena can be explained using linguistic categories. Separately, a description of the methodological components of the concept of mass communication of the scientist has been made: it is argued that by means of mass culture a certain cultural code opposite to the transmitter code can be formed at the receiving instance. The results of the interpretation of the primary data of the sociological research project of the State University of Management have been presented, on the basis of which it can be concluded, that young people go beyond the important sociocultural norms of communication, which can cause distortion of signs and image codes of the virtual interlocutor and lead to a dangerous situation. The conclusion about the possibilities of using the scientific method of Umberto Eco in digital sociology for social diagnostics of the content and specificity of communications on the Internet, which allows to represent different aspects of your real or desired “I”, to create identities through many virtual characters, has been substantiated.